Polyradiculoneuropathy and neurocysticercosis: Case report - Agapejev, Svetlana [UNESP]; Silva, Maria Dorvalina D.A. [UNESP]; Resende, Luiz Antonio de Lima [UNESP] (FapUNIFESP (SciELO), 1996)
Report of a patient with the hydrocephalic and meningoencephalitic form of neurocysticercosis who simultaneously developed polyradiculoneuropathy and intracranial hypertension syndrome during the first week of treatment with albendazole. Etiologic agents associated with polyradiculoneuropathy related in the literature are cited. Some comments about the possible physiopathogeny of this entity in the presence of cysticercosis are also done. It is mentioned another case who presented polyradiculoneuropathy as the only manifestation of a probable cysticercosis of the nervous system. In this presented case, including the neurocysticercosis and even a mere coincidence of facts, some factors can have a relationship with the appearance of polyradiculoneuropathy as the surgical stress, the stress due to the severity of the clinical picture and the possible side effect of albendazole.
Keywords: albendazole; cysticercosis; neurocysticercosis; polyradiculoneuropathy; adult; case report; guillain barre syndrome; human; intracranial hypertension; male; pathophysiology; Adult; Albendazole; Anthelmintics; Central Nervous System Diseases; Cysticercosis; Humans; Male; Polyradiculoneuropathy